Distribution and prognostic impact of coronary artery disease and nonischemic cardiomyopathies in patients with electrical storm - Müller, Julian; Behnes, Michael; Ellguth, Dominik; Schupp, Tobias; Taton, Gabriel; Reiser, Linda; Engelke, Niko; Borggrefe, Martin; Reichelt, Thomas; Kern-Bollow, Armin; Kim, Seung‑Hyun; Barth, Christian; et al. (Coronary artery disease, 2022)
Background: he distribution and prognostic impact of coronary artery disease (CAD) in ES are still under debate. Methods: Consecutive ES patients with implantable cardioverter-defibrillator (ICD) were included retrospectively from 2002 to 2016. Three analyses were applied to characterize ES patients: (a) ES patients without CAD (non-CAD), (b) ES patients with CAD (CAD), and (c) diagnostic findings assessed by coronary angiography (CA) at the time of ES (immediate CA). CAD was compared with non-CAD ES patients, and progressive CAD was compared with stable CAD ES patients. The primary endpoint was all-cause mortality at 2.5 years. Secondary endpoints were the composite endpoint of first recurrent ventricular tachyarrhythmias and appropriate ICD therapies, and recurrence of ES (ES-R) at 2.5 years.Results: Within a total of 87 consecutive ES patients. CAD was present in more than two-thirds (67%). However, only 52% patients underwent immediate CA at the time of ES. Here, 84% had CAD, of which 39% revealed progressive CAD with the need of target vessel revascularization (TVR) or cardiac transplantation (n = 1). At long-term follow-up, neither the presence (or absence) of CAD (41% vs. 34%; log rank P = 0.708) nor of progressive CAD (33% vs. 26%; log rank P = 0.372) was associated with all-cause mortality at 2.5 years, and further secondary endpoints including the composite of recurrent ventricular tachyarrhythmias plus appropriate ICD therapies, or ES-R. Conclusion: In ES patients, CAD was more common than non-CAD-related cardiac diseases, accompanied by an underinvestigated rate of CA despite increasing rates of progressive CAD. CAD had no prognostic impact in ES.